Current lung cancer screening practice amongst general practitioners in Western Australia: a cross‐sectional study. Issue 1 (3rd January 2018) - Manners, David; Wilcox, Helen; McWilliams, Annette; Piccolo, Francesco; Liira, Helena; Brims, Fraser
Abstract: Lung cancer screening with low dose computed tomography (LDCT) is recommended in the USA and Canada for high‐risk smokers but not in Australia. We administered a cross‐sectional survey to Western Australian general practitioners (GP). The majority (64/93, 69%) reported requesting a screening chest X‐ray (42/93, 45%) and/or LDCT (38/93, 41%) in the past year. LDCT screening was more common if the GP had received education from radiology practices (odds ratio (OR) 2.81, P = 0.03) or if they believed screening is funded by the Medical Benefits Scheme (OR 3.57, P = 0.02). Lung cancer screening with LDCT is occurring outside a coordinated programme, contrary to Australian guidelines.